Integrasi Teknik Coaching Menyusui dengan Konseling Laktasi Terhadap Peningkatan Keberhasilan Inisiasi Menyusu Dini (IMD) Pada Ibu Pasca Persalinan - Haruna, Sri Rahmah; Nusdin, Nusdin (Journal of Islamic Nursing, 2025)
Integration of breastfeeding coaching and lactation counseling is expected to strengthen maternal readiness and confidence in implementing early initiation of breastfeeding (EIBF). This study aimed to determine the effectiveness of integrating breastfeeding coaching with lactation counseling on the success of EIBF among postpartum mothers. A quasi-experimental study with a two-group posttest-only design was conducted involving 60 postpartum mothers, divided equally into intervention and control groups. The intervention group received integrated breastfeeding coaching and lactation counseling, while the control group received conventional education. EIBF success was measured using an observation checklist. The results showed a higher proportion of successful EIBF in the intervention group compared to the control group. The integration approach effectively improves EIBF outcomes and can be recommended as an evidence-based strategy in maternal and neonatal care services.